Insurgent - Roth, Veronica (London HarperCollins Children's Books, 2012)
One choice can transform you -- or it can destroy you. But every choice has consequences, and as unrest surges in the factions all around her, Tris Prior must continue trying to save those she loves -- and herself -- while grappling with haunting questions of grief and forgiveness, identity and loyalty, politics and love. Tris's initiation day should have been marked by celebration and victory with her chosen
Keywords: Social classes -- Families -- Dystopias -- Identity (Psychology) -- Courage -- Identity (Philosophical concept)